Role of TGF-β1 in the behavior disorders - Depino, Amaicha Mara (2015)
Transforming growth factor 1 (TGF-β1) is an anti-inflammatory cytokine that is expressed in different regions of the mammalian brain, and at all developmental ages. This cytokine can modulate neuron differentiation and survival, and also participate in the tissular response to injury. Based on clinical evidence, different approaches have been used to study the role of TGF-β1 on modulating brain function and behavior. Here, we review evidence showing a role of TGF-β1 in circadian rhythms, locomotion, sociability and depression-related behaviors. For these behaviors, suprachiamatic, hippocampal and cerebellar expression of TGF-β1 have been manipulated. Further studies are required to extend these results to other brain regions and different behaviors, but so far evidence points to a role of TGF-β1 on behavior disorders such as schizophrenia, depression and autism.